The effects of achievement goals on performance, enjoyment, and practice of a novel motor task - Kavussanu, M.; Morris, R. L.; Ring, C. (Journal of Sports Sciences, 2009)
We examined the effects of trichotomous achievement goals on performance, enjoyment, and practice of a golf-putting task. Male (n = 39) and female (n = 63) undergraduate students participated in the experiment in exchange for course credit. Participants were assigned to a mastery, performance-approach, or performance-avoidance goal condition and completed seven blocks of 10 trials (one for baseline, four for the experimental phase, and two for the transfer phase) of a golf-putting task. Distance from the target was measured and performance measures of accuracy and consistency were calculated. Self-reported enjoyment during the baseline and experimental phases and practice during a 5-min period before and following the experimental task were also assessed. Performance accuracy and consistency improved similarly among the three groups. Individuals in all three conditions reported enjoying the task to the same extent. Mastery participants practiced for longer than performance-approach participants during the practice period. Performance-avoidance participants did not differ significantly from the other two groups. The three goals were equally effective in promoting performance and enjoyment of the golf-putting task. The differential practice results for the two performance goals suggest that they should be considered separately.